PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI PIZZA HUT DELIVERY ARUNDINA CIBUBUR - Aris Budiono; Astri Yuliana (LPPM Universitas Asa Indonesia, 2021)
This study aims to analyze product quality, price perception and promotion on purchasing decisions at Pizza Hut Delivery Arundina Cibubur. The population in this study were customers of Pizza Hut Delivery Arundina Cibubur, using primary data in a questionnaire. Data were taken using the accidental sampling method for as many as 120 respondents. In addition, 20 respondents were intended for validity testing, and the rest were designed for research calculations. The data analysis method used in this research is multiple linear regression analysis. The analysis includes the validity and reliability test, classical assumption test, multiple regression analysis, t-test and F test, and analysis of the coefficient of determination (R2). The results of this study stated that simultaneously the three variables were declared to affect purchasing decisions. Product quality partially does not affect purchasing decision variables, while price perception and promotion variables significantly affect purchasing decisions at Pizza Hut Delivery Arundina Cibubur.